English as Medium of Instruction Implementation for Communication and Sustainability in 4.0 Era - Shiyrah Theosebes Sela; Joice Yulinda Luke (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
Globalization spreads fast around the world put English language become a-must-have skill. Almost all people use English in the teaching learning process, communication, transferring soft skills and hard skills, showing social status in communities, business transactions, political purposes, even on the some medicine instruction, food ingredients, mechanic usage instruction, and many more. The language is used to various purposes, as for online and offline communication. During this corona virus pandemic, English as a Medium of Instruction is implemented mostly in online educational institutions. English as Medium of Instruction is also applied to any subjects in universities in non-English speaking countries. This research focuses on the implementation of English as Medium of Instruction for communication and sustainability in 4.0 era for non-English lecturers in a private university in Indonesia. The survey questionnaires used online link was randomly sent to 53 lecturers as informants. The aim of using online link to support data gathering is to ensure all information required can be collected on time, faster and efficiently. The data was quantitatively presented and qualitatively analyzed. The data collected were information on how essential English related to English of Medium of Instruction implementation for communication & sustainability in 4.0 era, including the challenges faced by non-English lecturers in fully English as Medium of Instruction classrooms. The findings of this research provide updated information regarding the learning needs and the effective teaching-learning method in implementing EMI for communication and sustainability in 4.0 era.